PENGARUH GAYA BELAJAR VISUAL DAN AKTIVITAS BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS IX DI SMP NEGERI 4 KOTA PROBOLINGGO - Susetyo Budi Mintarti (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
This study aims to know the correlation between visual learning style and learning activities toward learning achievement of ninth graders at SMP Negeri 4 Probolinggo. The respondents of this research were ninty (90) student of nineth grade of SMP Negeri 4 Probolinggo. The results showed that visual learning style and learning activities influenced learning achievement positively.